A Strategy of Attrition through Enforcement: The Unmaking of Irregular Migration in Malaysia. Issue 2 (August 2017) - Chin, Low Choo
This article reviews Malaysia's attempt to achieve zero migration irregularity by focusing on workplace enforcement, and examines how Malaysia's migration control has become a struggle between the state and employers. Applying the framework of "enforcement through attrition, " this research examines three newly introduced principles governing workplace enforcement: employer sanctions, the Strict Liability Principle, and the Employers' Mandatory Commitment. The shift to employers in Malaysia's attrition landscape aims to control illegal employment, thereby frustrating the friendly environment to affect migrants' behaviour. The Malaysian experience suggests that increasing legal consequences for employers hiring undocumented workers runs parallel with making them accountable for the welfare of their foreign workers, thus ensuring better protection of migrant rights. Drawing upon data from semi-structured interviews, government documents, regulations and online news media, this paper empirically analyses the new policy's effects and implications. The findings suggest this deterrence model has a positive effect on the existing documented migrants, demonstrating an increase in both legal employment and in wages for the existing legal migrant workforce.